2018
DOI: 10.1002/pts.2422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan‐propolis edible coatings on stability of refrigerated cachama (Piaractus brachypomus) vacuum‐packed fish fillets

Abstract: The effect of chitosan‐based coatings containing ethanolic extracts of propolis (EEPs) on the quality of chill‐stored, vacuum‐packed fillets of cachama, an emerging aquaculture species of fish native to the Amazon basins, was evaluated. Coatings were prepared by adding propolis to chitosan following two different strategies: (1) incorporation of microencapsulated EEP and (2) direct incorporation of EEP. Fillets were dip‐coated, vacuum‐packed in medium‐oxygen barrier bags, stored at 4°C, and their quality was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…Different researches have also shown that EOs by having phenol compounds and tocopherols are able to retard the oxidation (Ariaii, Tavakolipour, Rezaei, Elhami Rad, & Bahram, ; Duan, Jiang, Cherian, & Zhao, ). It has been reported that the secondary lipid oxidation compounds in Cachama fish coated with chitosan–propolis was 12%–15% lower compared with control samples (Piedrahíta Márquez et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different researches have also shown that EOs by having phenol compounds and tocopherols are able to retard the oxidation (Ariaii, Tavakolipour, Rezaei, Elhami Rad, & Bahram, ; Duan, Jiang, Cherian, & Zhao, ). It has been reported that the secondary lipid oxidation compounds in Cachama fish coated with chitosan–propolis was 12%–15% lower compared with control samples (Piedrahíta Márquez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although no difference between CNP‐coated treatments and fillets loaded with fennel EO was observed, the samples containing both EO and CNPs had the lowest PV, so that after 27 days of storage the PV was 18.95 m eq /kg of fish oil. The maximum permissible PV for fish oils is 5 m eq /kg (Piedrahíta Márquez, Fuenmayor, & Suarez Mahecha, ), from which all samples except the control and MAP were below the acceptable level, up to 6 days of storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edible coatings solutions were prepared as described by Piedrahíta, Fuenmayor, and Suarez (2019) with slight modifications. Initially, 4 g of chitosan with a degree of deacetylation of approximately 80% (Quimer, Brazil) was dissolved in 200 ml of 1% (v/v) lactic acid solution (CIMPA S.A.S) and stirred for 2 hr at 40°C.…”
Section: Methodsmentioning
confidence: 99%
“…Typical colonies were counted and the values were transformed into log CFU/g of cheese sample (Kingcha et al., 2012). To analyze mesophilic bacteria (Piedrahíta et al., 2019), psychrophilic bacteria, and total molds and yeasts (Fajardo et al., 2010), 10 g from the cheese was homogenized in 90 ml of peptone water by stomacher for 2 min. Aliquots of 1 ml of 10‐fold serial dilutions were pipetted into Petri dishes.…”
Section: Methodsmentioning
confidence: 99%